Optimization of Nested PCR Method for Vibrio parahaemolyticus AHPND Detection in Vannamei Shrimp (Litopenaeus vannamei) - Anissa, Ratih Khairul; Lisdiana, Lisa; Widyayanti, Anita Tri (LenteraBio : Berkala Ilmiah Biologi, 2023)
Vannamei shrimp culture has a high risk of contracting diseases, one of which is Acute Hepatopancreatic Necrosis Disease (AHPND) caused by Vibrio parahaemolyticus strain AHPND. This disease is highly contagious and has a mortality rate of up to 100%. Early detection is needed to predict deployment and reduce the risk of production failure. Detection can be carried out using the AP4 nested PCR method, but many PCR results are not optimal, so it is necessary to optimize the method. The purpose of this study was to determine the optimal primer concentration and annealing temperature of AP4 nested PCR method. The steps of the research included DNA extraction, amplification, and electrophoresis. In the amplification, optimization of primer concentration (2.5 μM, 5 μM, and 10 μM ) and annealing temperature (53°C, 58°C, and 63°C) was carried out. The amplification results for each treatment obtained a band of 230 bp, no smears, primer dimers and mispriming, but had different thickness variations. At annealing temperature of 58°C and primer concentration of 5 μM, the best results were obtained in the form of the thickest and single band compared to the other treatments. In conclusion based on these results that the best optimization method is using an annealing temperature of 58°C and 5 μM of primer concentration.